Effect of International Migration on Unemployment and Poverty in Nigeria: 1985 - 2020 (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
This study examined the effect of international migration, on unemployment, and poverty in Nigeria from 1985-2020). The data used in this study were obtained from Central Bank of Nigeria (CBN) statistical bulletin (2020), World Development Indicators and the KOF Swiss Economic Institute. These comprises of annual data of the following variables unemployment rate and poverty index serves as the dependent variables in the two models respectively while international migration remittances, Globalization Index, and Adult literacy rate serves as the independent variables. The test statistics used in the analysis of data was; Auto Regressive Distributed Lag (ARDL). The results showed that; International migration proxy by international migration remittances has a positive and significant relationship with unemployment and a negative and significant relationship with poverty in Nigeria. it was recommended that; Enlightenment campaigns directed at recipients of remittances regarding the benefit of investing remittance money in small and medium scale enterprises be encouraged rather than using the money as a substitute for labor income; Nigerian governments and their agencies should manage the economy properly and put up policies that can help to eliminate poverty which has been identified as the major force that pushes its citizens into migration. In other words, the formulation of National Migration Policy in 2015 is not enough. There is need to develop an accompanying policy on poverty reduction to propel the migration policy to success; the need for Government to encourage globalization, by embarking on trade liberalization policies in order to accelerate and sustain industrial growth and in turn a reduce poverty. They should also monitor the movement of factor inputs as well as imported and exported goods both in and out the country by way of creating a well secured boarders across the country and a strong and efficient Custom Officials.